Culture Shock and the Paradox of Adaptation: A Phenomenological Study on Resilience and Self-Identity Reconstruction among Interregional Students - Taroreh, Anggraini; Tiwa, Tellma Mona; Sengkey, Marssel Michael (Universitas Pendidikan Mandalika, 2025)
This study aims to explore the phenomenon of culture shock experienced by students from different regions at Universitas Negeri Manado using a phenomenological study approach. The main focus of this research is to describe the experience of culture shock and to explore strategies for developing resilience and reconstructing the self-identity of students from different regions during the adaptation process in a new environment. The research subjects consist of 3 (three) individuals with the following criteria: the subjects are students from different regions who have been studying for at least 3 (three) semesters at Universitas Negeri Manado, possess clear experiences of culture shock, both positive and negative during their studies, originate from various regions and diverse cultural backgrounds, and demonstrate a measurable level of resilience in coping with culture shock. Data collection methods include observation and in-depth interviews, which are thematically analyzed to identify patterns of experiences and adaptation strategies used. The results indicate that students from different face various challenges such as cultural differences, language, social norms, weather, and food, which trigger feelings of alienation, stress, and frustration. Nevertheless, they develop effective adaptation strategies, namely building social support, learning the local language, and appreciating and accepting the new culture. Additionally, self-reflection, increased self-confidence, self-efficacy, positive affirmation, and self-awareness also play important roles in strengthening resilience and helping them reconstruct their self-identity. This study is expected to provide theoretical and practical contributions in the development of policies and support programs capable of assisting students from different in facing culture shock, especially in the context of cultural diversity in Indonesia.